The influence of competitive level on the sports specific performances of wheelchair basketball players - Gök, E.; Makaraci, Y. (Kinesiologia Slovenica, 2022)
The main purpose of the present study is to evaluate the physical characteristics and field test performances of wheelchair basketball (WB) players according to the competitive level (CL). The second goal was to compare the results of physical characteristics and field test performances of WB athletes with different functional classification (FC) scores. Seventy-five (70 males- 5 females) proffesional WB athletes took part in this study. The athletes were divided into two CL: Elite (Super and First League)- Sub-elite (Second and Third League) categories. Players are also grouped into two FC categories: Category A (classes from 1.0 to 2.5)- Category B (classes from 3.0 to 4.5). Players underwent anthropometric measurements, bilateral grip strenght and took field tests in separated sessions. Field tests were evaluated with 20-meter sprint, slalom without the ball, slalom with the ball, zone shot, lay up, passing accuracy, and shuttle run test. Between group differences and correlations were computed to assess the study hypotheses. Statistical differences were observed when the bilateral grip strength and field test performances of WB athletes were examined according to the CL and FC categories. The sitting height and FC score were found to be the indicators that best expressed the field test performances. It has been determined that the field performance in WB differs according to the CL. Besides; since the hand wrist area is intensively used in many movements in WB, a common measurement such as grip strength should be evaluated as a performance criterion in WB athletes.